Export production, hedging exchange rate risk: the duopoly case - Udo Broll; Jack E. Wahl; Christoph Wessel (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2008)
This paper studies a Cournot duopoly in international trade so that the firms are exposed to exchange rate risk. A hedging opportunity is introduced by a forward market where the foreign currency can be traded on. We investigate two settings: First we assume that hedging and output decisions are taken simultaneously. We show that hedging is just done for risk managing reasons as it is not possible to use hedging strategically. In this setting the well-known separation result of the competitive firm holds if both firms have the hedging opportunity. In the second setting the hedging decisions are made before the output decisions. We show that hedging is used not only to manage the risk exposure but also as a strategic device. Furthermore we find that no separation result can be stated.
Keywords: F10; F11; F30; F31; 330; Exchange Rate risk; hedging; exports; duopoly; Wechselkursrisiko; Export; Hedging; Duopol; Außenwirtschaftstheorie; Theorie